Augmented lectures: benefits of supporting physics teaching with the theatre - Giliberti, M; Persano Adorno, D; Pizzolato, N; Battaglia, O R; Fazio, C (Journal of physics. Conference series, 2019)
Young generations are less and less interested in studying STEM subjects. For this reason, numerous studies have strongly suggested a change in the methods scientific knowledge is developed in the learners, through the use of alternative and more creative strategies. In recent decades a strong interaction between scientific subjects and the arts has been established by means of theatre. The objective is to bring science to students and the public in ways that are engaging, instructive, artistic and, always, content-driven: the medium is the arts; the message is the joy of science. When we talk about Physics in a theatre show, are we only making a good dissemination or are we also transmitting contents and changing the nature of science view of the audience? In order to address this question, after the augmented lecture titled "There are no things inside things", we invited the audience to answer both to a closed-answer survey about the performance and to an open-ended questionnaire focused on the theme "what is understanding?", in terms of physics contents and NoS view. In this contribution, we analyze and discuss the answers provided by the people who have attended the augmented lecture. The analysis of the answers shows that the performance was appreciated as an example of showmanship in facing the wide-range cultural message of physics.